2007
DOI: 10.5511/plantbiotechnology.24.503
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of three halide methyltransferases in Arabidopsis thaliana

Abstract: Methyl chloride and methyl bromide, which contribute to the destruction of the stratospheric ozone layer, are mainly emitted from natural sources. It was recently reported that tropical and subtropical plants were the largest sources of methyl chloride. Furthermore, the involvement of the gene HARMLESS TO OZONE LAYER (HOL) in methyl halide emissions from Arabidopsis thaliana was demonstrated. However, neither the physiological significance of the methyl chloride emission nor the biochemical properties of HOL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…Because the gene disruption eliminated almost all of the methyl halide emissions from the mutants, the gene was revealed to be involved in methyl halide synthesis and was designated HOL (HARMLESS TO OZONE LAYER; denoted as AtHOL1 in our studies) based on the mutant phenotype (18). Recently, we identified AtHOL1 homologs AtHOL2 and AtHOL3 in Arabidopsis, and we demonstrated biochemically that the three recombinant AtHOLs have SAM-dependent methyltransferase activities (19). In this study, reverse genetic and biochemical analyses of all AtHOL isoforms revealed that AtHOL1 in vivo is involved in the methylation of NCS Ϫ produced by glucosinolate hydrolysis.…”
mentioning
confidence: 89%
“…Because the gene disruption eliminated almost all of the methyl halide emissions from the mutants, the gene was revealed to be involved in methyl halide synthesis and was designated HOL (HARMLESS TO OZONE LAYER; denoted as AtHOL1 in our studies) based on the mutant phenotype (18). Recently, we identified AtHOL1 homologs AtHOL2 and AtHOL3 in Arabidopsis, and we demonstrated biochemically that the three recombinant AtHOLs have SAM-dependent methyltransferase activities (19). In this study, reverse genetic and biochemical analyses of all AtHOL isoforms revealed that AtHOL1 in vivo is involved in the methylation of NCS Ϫ produced by glucosinolate hydrolysis.…”
mentioning
confidence: 89%
“…Methyl iodide has been observed to be produced by bacteria [14], fungi [9] and plants [11], and is preferentially generated relative to the other methyl halides in most cases. Genetic sequences and enzymatic mechanisms for bacterial consumption of methyl chloride and methyl bromide have been identified [15], as well as a suite of homologues for methyl halide production in plants [16]. There remains uncertainty regarding whether all primary mechanisms for monohalogenated metabolism have been identified [11,17].…”
Section: Introductionmentioning
confidence: 99%
“…A genetic analysis of Arabidopsis T-DNA insertion mutants clari ed that the HARMLESS TO OZONE LAYER gene (HOL; AtHOL1 in our study) is involved in the emission of methyl iodide as well as methyl chloride and methyl bromide, which contribute to the destruction of the stratospheric ozone layer (Rhew et al 2003). Arabidopsis possesses two further HOL paralogs, AtHOL2 and AtHOL3 (Nagatoshi and Nakamura 2007). Biochemical analyses of the three AtHOL proteins showed that they have SAMdependent methyltransferase activities toward iodide ions as well as chloride, thiocyanate, and hydrosul de ions .…”
mentioning
confidence: 99%
“…The second PCR was performed using the inner primers (5′-ATG GCG TCG GCG ATC GT-3′ and 5′-CAC TCC TTG TTC GCA GCA TA-3′ for OsHOL1, 5′-ATG AGC TCG TCG GCG GC-3′ and 5′-TAA AGA AGG GAT GCA GCG TT-3′ for OsHOL2). Each of the cDNA fragments was cloned in-frame with an N-terminal glutathione S-transferase (GST) tag into an expression vector pDEST15-T that was modified to possess a thrombin recognition site at the C-terminus of GST in pDEST15 (Invitrogen) (Nagatoshi and Nakamura 2007). e recombinant proteins digested with thrombin Copyright © 2012 The Japanese Society for Plant Cell and Molecular Biology had 15 extra amino acids (GSTSLYKKAGSEFAL) at the N-terminus of each OsHOL protein.…”
mentioning
confidence: 99%